2022
DOI: 10.1007/s40618-022-01799-2
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of weekly subcutaneous treatment with semaglutide in a cohort of Italian diabetic patients

Abstract: Purpose Registered trials and real-world evidence (RWE) studies provided evidence on the efficacy of once-weekly (OW) semaglutide on hyperglycaemia and cardiovascular risk factors as add-on or de-novo treatment in type 2 diabetes (T2D). Methods In a retrospective analysis of electronic data files from 258 T2D patients, this RWE study aimed to explore the impact of OW semaglutide on biochemical and anthropometric outcomes after 6 and 12 months in patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
7
10
0
Order By: Relevance
“…The current study data showed that baseline HbA1c and disease duration of diabetes were predictors of effectiveness. The results of several real-world studies have shown that higher baseline HbA1c was associated with a greater effect of OW semaglutide [20,24,25], consistent with our results (Table 2, Supplemental Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study data showed that baseline HbA1c and disease duration of diabetes were predictors of effectiveness. The results of several real-world studies have shown that higher baseline HbA1c was associated with a greater effect of OW semaglutide [20,24,25], consistent with our results (Table 2, Supplemental Fig. 1).…”
Section: Discussionsupporting
confidence: 92%
“…1). Marzullo et al reported that the shorter duration of diabetes was a significant predictor of a good response after 6 months OW semaglutide induction [25]. Since the retention of GSIS capacity in patients with T2DM is inversely correlated with the duration of diabetes [26], it is speculated that longer duration is responsible for the attenuated effect of insulin secretagogues.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that relevant clinical benefits on metabolic parameters and CV risk factors have been achieved also with intermediate dosage. These results are consistent with those of other real-world studies based on cohorts followed in other settings, all documenting effectiveness and safety of OW semaglutide (32,35,(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 89%
“…6,7 The results of the SURE Italy study are consistent with efficacy and safety data from the SUSTAIN RCTs [13][14][15][16][17][18] and the SURE studies in Canada, 22 Denmark/Sweden, 23 Spain, 24 Switzerland 25 and the UK 26 and pooled analyses of these studies, 27 the latter of which showed that OW semaglutide use in routine clinical practice was associated with clinically relevant improvements in glycaemic control (-0.2-to -2.5%-point) and body weight (-2.5 to -5.6 kg) and was well tolerated in a wide range of adults with T2D. Regional, small and retrospective RW observational studies of semaglutide in clinical practice in Italy have shown similar results, [28][29][30][31][32] increasing the body of evidence for the benefits of OW semaglutide treatment in adults with T2D in RW settings. Moreover, as reported by Di Dalmazi et al, semaglutide was associated with greater reductions in HbA1c and weight versus the maximum doses of OW exenatide and dulaglutide that are available in Italy.…”
Section: Safetymentioning
confidence: 80%